Analyzing the effects of uncertainties on fatigue life by using interval numbers - Erdolen, Ayse; Kutug, Zafer (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2024)
Small fatigue cracks in engineering structures can lead to severe results, such as sudden and destructive damage with increasing growth under time-varying. Defining the Fatigue Crack Growth (FCG) life within a reliable interval is highly critical for a system to operate under working loads. Therefore, the sudden occurrence of such damage can be prevented by predicting the appropriate maintenance and service intervals. On the other hand, there are some uncertainties in determining the fatigue performance in the design process due to insufficient knowledge and generalizations. In this study, the effects of the uncertainties in material, load and geometrical parameters in predicting the fracture mechanics-based FCG life have been presented using the Interval Analysis Method (Interval Numbers). Therefore, the aim was to obtain reliable interval values specified with lower and upper limits for FCG life by considering the uncertainties of different types of parameters. The proposed method has been applied to predicting the FCG life of a plate having EN-GJS600-3 material properties. Using interval toolboxes developed for the MatLab interface in terms of mathematical operations enabled the proposed method to run with the computer code prepared specifically for interval arithmetic.
Keywords: Fatigue; fatigue crack growth; uncertainty; interval analysis; Paris law; CRACK-GROWTH; RELIABILITY; PROPAGATION; STIFFNESS; Engineering